STUDI ZONASI PEMIJAHAN DAN ASUHAN KERANG Geloina erosa DI PERAIRAN PAYAU KAWASAN LEUPUNG KABUPATEN ACEH BESAR - M. Ali S (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
The zone of hatching anf nursery of Gelonia erosa in brackish area of Leupung is unknown. Therefore, the study of the zones of both activities, hatching and nursery, must be done.  The study was aimed to determine the zonation of hatching of Gelonia erosa, indicators for hatching and nursery zones, and strategies of management of both zones in the brakhish area Leupung. Data was collected in three locations; Location I (River Leupung), Location II ( River Reuleng), and Location III (River Lhok Kulam). The methods of collecting data were Jarnis Larva Collector used for larva collection, in-situ used to collect biophysic data, and sweep area and destructive methods used to collect the young and mother of the species. It was found that in downstream of Location I, dominated by Nypa fructicans, there were 24 larvas, 10 and 61 individuals of young and mother of Geloina erosa respectivelly. Location II dominated by Nypa fructicans  and Fimbristilys sp had 10, 14, and 49 individuals of larva, young, and adult of Geloina erosa whereas Location III dominated by fructicans  and Fimbristilys sp as well had 12 and 65 individuals of young and adult of Geloina erosa. It can be concluded that the zone of hatching can be determined by the presence of larva, young and adult of Geloina erosa with fully-grown of gonad while the determination of nursery zone is relied on the presence of young and male and female adults of Geloina erosa with well-matured gonads.